Aplikasi Media Pembelajaran Tematik Kelas V pada SDIT Al-Kautsar - Ratih Teni Kusumalia; Nuraini Purwandari (UNIVERSITAS KALBIS, 2022)
SDIT Al-Kautsar is having problems related to the implementation of thematic learning, such as difficulty to understand material explained by the teacher. Although they have used learning media as a tool on learning process, the use of the media still considered to be less effective and interactive. Based on these problems, this study aims to design and build an alternative thematic learning media application for grade 5th. The research uses Multimedia Development Life Cycle with six stages in it, namely concept, design, material collecting, assembly, testing, and distribution. The learning media was built with Adobe Animate CC and Actionscript 3.0. The results of this study is desktop-based thematic learning media for grade 5th at SDIT Al-Kautsar, which obtain 88% in the feasibility test, so the application is very feasible to be implemented.